Effect of trichloroethylene (TCE) on female albino mice and their early embryos - El-Shershaby, AM; El-Balshy, RM; Abd El-Hady, SI; Abou-Rashed, NM (International Journal of Biological Research, 2014)
The present study investigates the effects of different doses of "trichloroethylene" TCE on pregnancy, early embryos on days 6 and 8 of pregnancy. The experimental females (90 virgin females) were divided into three groups; the first one (C) was the control that treated with the solvent only (corn oil), the second (G1) and the third (G2) treated groups with low (24 mg/kg) and high (240 mg/kg) dose of TCE, respectively. Oral administration of TCE to female mice once daily for a period of 21 days before mating and till 5th and 7th day of pregnancy, caused a significant decrease in the body weight for non-pregnant females and weight gain for pregnant females. The percentage of survival, mating and abortion were also significantly decreased by TCE treatment for pregnant females. Histological examination for the obtained 6 and 8 day mice embryos from treated mothers showed some histopathological alterations in compared with the normal control embryos. These alterations indicated that TCE treatment resulted in retarded, delayed and deformed embryos. The results suggest that TCE has teratogenic and embryo toxic effects on the early development of mice embryos following a short-term of exposure. Keywords: Trichloroethylene, Mating, 6th and 8th Day Mouse Embryo, Histopathology, Early Developmental Stages.